SHARIA LOCAL FUNDING (SALAF CARD): INNOVATION ON SMES FUNDING USING ISLAMIC BOARDING SCHOOL VENTURE CAPITAL - Nila, Faridatun; Utama, R. Wahyu Agung; Mawardi, Imron; Fudholi, Moh.; Muhtadi, Ridan (Jurnal Ekonomi Islam, 2019)
Islamic boarding school is one of the educational institutions that have a strong network. Until now, there were 27,230 Islamic boarding schools scattered throughout Indonesia. Today, the function of Islamic boarding schools is not only functioning as an Islamic-based educational institution but also Islamic boarding schools has a function as a social institution. Islamic boarding schools are considered potential to become the basis of empowerment local people's economy and the center of economic development of the people in the regions, both in the form of Islamic financial institutions or Islamic boarding school cooperation. Law in Indonesia, No.33 of 2014 concerning guarantees on halal products provides significant opportunities for innovative product development given the huge potential of Indonesia's Muslim population. In the process, the requirement to use halal certification in trade as mandated by national law carries a dilemma on halal industrial players as well as micro, small and medium enterprises (SMEs). The problem of capital and funding is key problem. This qualitative paper offers a literature review. The purpose of this paper is to understand how innovative funding models are through Islamic Boarding School venture capital the company spurred the growth and development of the halal industry. The Sharia Local Funding Card (SALAF) is innovative Mudharabah and Musyarakah transaction models at Baitul Mal Wattamwil, which are realized in sustainable funding with the Sharia business capital company for halal industry players. Allocation of profit sharing is based on the contract by specifying several parts other than cards as productive deposits. These deposits will be managed as productive stimulus funds for maintenance of halal certification, training, and business assistance, and the SALAF card balance itself. SALAF card is an innovative model that has a sustainable funding agreement that involves several stakeholders to improve productivity, growth, and presence of halal products in the nation trade arena.  Keywords: financing, SMES, SALAF card, Islamic Boarding School venture capital